2008
DOI: 10.1007/s11670-008-0290-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of vascular endothelial growth factor in benign and malignant tissues of breast

Abstract: Objective: To detect the expression of vascular endothelial growth factor (VEGF) and microvessel density (MVD) count in breast benign affection, breast atypical hyperplasia and breast carcinoma in situ, and to clarify the relationship between VEGF expression, MVD and the clinicopathological features of these diseases. Methods: The expression of VEGF and MVD count in 115 cases breast benign diseases (including 40 breast fibroid tumor,40 breast cystic hyperplasia and 35 intraductal papilloma, 19 breast atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In Germany, Konecny and his group carried out a study and determined that 77.6% of cases tested positive for ER/PR. [19] Our findings are quite similar to their findings. The association between the expression of ER, PR, and VEGF was evaluated in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Germany, Konecny and his group carried out a study and determined that 77.6% of cases tested positive for ER/PR. [19] Our findings are quite similar to their findings. The association between the expression of ER, PR, and VEGF was evaluated in this study.…”
Section: Discussionsupporting
confidence: 92%
“…[22] Konecny and his workers (2004) also conducted a study in Germany and found that 18.7% of cases were HER-2/neu positive. [19] In India, a researcher reported that VEGF expression significantly correlated with the overexpression of HER-2/neu. [23] But, this study showed no such relationship.…”
Section: Discussionmentioning
confidence: 99%